PERBANDINGAN EFEKTIVITAS MADU DAN EKSTRAK ETANOL DAUN KELOR (MORINGA OLEIFERA LAMK) TERHADAP PERCEPATAN PENYEMBUHAN LUKA BAKAR DERAJAT II PADA TIKUS PUTIH JANTAN (RATTUS NORVEGICUS STRAIN WISTAR) SECARA MAKROSKOPIS - Muhammad Azmi Fanany; Andi Ipaljri Saputra; Wifa Nur Yasmin (Universitas Batam, 2024)
Background: Burns are damage to the skin or other tissues caused by high temperatures, radiation,electricity, or contact with chemicals. Healing by maintaining resistance that has potential to killbacteria at affordable prices is to use the active substances contained in honey and Moringa leaf.Methods: Research with True Experimental design by giving honey and ethanol extract of moringaleaves in gel preparation to affect the acceleration of second degree burn wound healing in ratsmacroscopically. With the design of